Peranan Orang Tua Dalam Peningkatan Prestasi Belajar Anak - Munirwan Umar (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2015)
The parents are the main responsible person in children aducation. The parents who determine the children`s future. But in acknowledge limitedness and possessed opportunity, so the parents ask for ather outsider helping to educate their children. The other outsider is the teachers at school. Nevertheless, the children have submitted at the schoo, the parent remaind to responsible to the success of their children aducation. The parents play important role in determining the success of their children education. The parent of role and responsibility among other can be realized by guiding the continuity of children learning at home according to learning program which has studied by children at school. The guiding of children learning continuity at home can be done by supervising and helping school tasks arrangement as well as completing instrument and infrastructure of children learning. Orang tua adalah orang yang bertanggung jawab utama dalam pendidikan anak-anak. Para orang tua yang menentukan masa depan anak. Namun dalam mengakui keterbatasan dan peluang yang dimiliki, sehingga orang tua meminta pihak luar lain membantu mendidik anak-anak mereka. Pihak lainnya adalah guru di sekolah. Namun demikian, setelah anak-anak dititipkan di sekolah, orang tua tetap untuk bertanggung jawab untuk keberhasilan pendidikan anak-anak mereka. Orang tua berperan penting dalam menentukan keberhasilan pendidikan anak-anak mereka. Induk peran dan tanggung jawab antara lain dapat diwujudkan dengan membimbing kelangsungan anak belajar di rumah sesuai dengan program yang telah dipelajari oleh anak-anak di sekolah belajar. Membimbing anak-anak belajar di rumah dapat dilakukan dengan mengawasi dan membantu pengaturan tugas sekolah serta menyelesaikan instrumen dan infrastruktur anak belajar. Kata kunci: Prestasi belajar, Orangtua